To Determine Efficacy Aspirin 150 mg vs 75 mg in Prevention of Preeclampsia and its Associated Complications - Samreen Ashraf; Habiba Sharaf Ali; Urooj Malik; Rozina Khatoon; Abida Shaikh (ziauddin University, 2024)
Background: Preeclampsia is a pregnancy-specific multisystem progressive disorder, characterized by a new onset of hypertension and proteinuria or significant end-organ dysfunction without proteinuria typically after 20 weeks. If not controlled, it can lead to adverse fetal outcomes. Aspirin a COX inhibitor can delay or prevent the onset of PE. Its effectiveness and safety in relatively higher doses (150mg) need to be investigated in the local population. To compare the two different low doses of aspirin 75mg vs. high dose of 150mg in moderate and high-risk women for prevention of preeclampsia and its associated complications. Methods: A Parallel arm randomized control open-label study was conducted at the Department of Obstetrics and Gynaecology of Ziauddin University Hospital Kemari, Karachi. A sample of 156 women, age >18 years, with moderate and high risk of Preeclampsia was selected consecutively. Random allocation of 78 women each was done to group A (75mg) versus group B (150 gm) of Aspirin. Patients with multifetal gestation, major fetal anomaly, thrombocytopenia, peptic ulcer, or bleeding disorder were excluded from the study. Ethical approval was sought from the ERC of Ziauddin University. Descriptive and analytical results expressed through SPSS software. Results: Both groups were comparable in terms of their basic demographics. The effectiveness of Aspirin 75mg was 53% compared to 70% of Aspirin 150mg in the prevention of pre-eclampsia among high-risk women. With 75mg Aspirin the incidence of PE decreased slightly with increasing age while with 150mg, it increased (P values = 0.141, 0.111 & 0.290 respectively. Higher rates of placental abruption (54.3%) accompanied by preeclampsia were seen in group A as compared to (21.7%; p value = 0.016) in group B. The incidence of pre-term delivery, miscarriage, NICU admission & superimposed eclampsia were higher with low-dose aspirin (P values = 0.779, NA, 0.210, 0.592, NA & 0.772 respectively). Conclusion: Aspirin 150mg in moderate and high-risk pregnancies starting at 11-14 weeks is more effective and safer than 75mg Aspirin reducing the incidence of Preeclampsia.